Why Black Flowers? An Extreme Environment and Molecular Perspective of Black Color Accumulation in the Ornamental and Food Crops - Ahmad, Sagheer; Chen, Jinliao; Chen, Guizhen; Huang, Jie; Zhou, Yuzhen; Zhao, Kai; Lan, Siren; Liu, Zhongjian; Peng, Donghui (Frontiers in Plant Science, 2022)
It is an admitted fact that pollinators are attracted to vibrant flower colors. That is why flower color is the key agent to allow successful fruit set in food or ornamental crops. However, black flower color is the least attractive to pollinators, although a number of plant species produce black flowers. Cyanidin-based anthocyanins are thought to be the key agents to induce black color in the ornamental and fruit crops. MYB1 and MYB11 are the key transcription factors regulating the expression of anthocyanin biosynthesis genes for black color accumulation. Environment cues have been the pivotal regulators to allow differential accumulation of anthocyanins in color regulation. Heat stress is one of the most important environmental stimuli that regulate concentration gradient of anthocyanins in various plant parts, thereby affecting the color pattern of flowers. The intensity and pattern of flower color accumulation determine the overall fruit set, thereby controlling crop yield and human food needs. This review paper presents comprehensive knowledge of black flower regulation as affected by high temperature stress, the molecular regulators of anthocyanin for black color in ornamental and food crops. It also discusses the black color-pollination interaction pattern affected by heat stress for food and ornamental crops.